2012
DOI: 10.1002/adfm.201202499
|View full text |Cite
|
Sign up to set email alerts
|

Virus‐Tethered Magnetic Gold Microspheres with Biomimetic Architectures for Enhanced Immunoassays

Abstract: In immunoassays, non‐specific bindings to biosensing surfaces can be effectively prevented by formation of biocompatible and hydrophilic self‐assembled monolayer (SAM) on the surfaces. A thin gold (Au) layer on magnetic microspheres, 15 μm in diameter, enables facile SAM formation and thereby accepts second layer of filamentous virus scaffolds for the immobilization of functional proteins. The merger of the virus and SAM‐Au protected microspheres not only provides exceptionlly dense antibody loading, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Production of BirA : His‐tagged BirA was prepared as previously described . Briefly, the pET21a‐BirA plasmid was transformed into E. coli BL21(DE3)pLysS, plated on LB‐agar with carbenicillin (100 µg mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Production of BirA : His‐tagged BirA was prepared as previously described . Briefly, the pET21a‐BirA plasmid was transformed into E. coli BL21(DE3)pLysS, plated on LB‐agar with carbenicillin (100 µg mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we showed that AP (AviTag, GLNDIFEAQK-IEWHE) fused to the p3 of fd-tet can be in vitro biotinylated by bacterial biotin ligase BirA, rendering site-specific and vertical immobilization of the virions on SAV microbeads. [4] Although high-density probe antibodies can be chemically conjugated on the virion surface using bioorthogonal Staudinger ligation, chemical modification of antibodies and virions inevitably decreased antigen binding capacity and increased hydrophobicity of the virion surface, necessitating extensive blocking steps to prevent nonspecific bindings. We thus seek to display genetically encoded IgGbinding domains while keeping the biotinylation motif at one of the virion tips for vertical immobilization.…”
Section: App3 But Not App7 Is In Vivo Biotinylated In Tg1 Cellsmentioning
confidence: 99%
See 3 more Smart Citations